Combined antitumor strategies mediated by hybrid polymeric and lipid-based nanosystems to hepatocellular carcinoma - Bushmalyova, Albina (2022)
Dissertação de Mestrado em Bioquímica apresentada à Faculdade de Ciências e Tecnologia